A Review on Analysis of TPA model for Secure Information Retrieval in Cloud Computing - Sahu, Nitin Kumar; Kumar Pal, Anuj (International Journal of Computer Sciences and Engineering, 2019)
Today’s businesses are interested in secure data and their applications can be accessible from anywhere using any device. It is able to achieve using cloud technology, but there are implicit challenges to making it realism. What can enterprise businesses do to reap the benefits of cloud technology while ensuring a secure environment for sensitive information? Recognizing those challenges is the first process to finding solutions that work. Increasingly many companies plan to move their local data management systems to the cloud and store and manage their product details on cloud servers. An accompanying issue is how to protect the security of the commercially confidential data, while preserve the ability to search the data. In this paper we are analysis of different securities scheme for encryption of item information and also for data search scheme in cloud computing.